Leisure time physical activity: a protective factor against metabolic syndrome development - Myong-Won Seo; Youngseob Eum; Hyun Chul Jung (BMC, 2023)
Abstract Purpose Physical activity (PA) is a modifiable factor in preventing/treating cardiometabolic disease. However, no studies have yet compared specific moderate-to-vigorous PA (MVPA) domains with the risk of metabolic syndrome (MetS) in detail. Here, the present study was conducted to examine the impact of different MVPA domains (leisure-time PA (LTPA) vs. occupational PA (OPA) vs. total MVPA) on the risk of MetS in Korean adults. Materials and methods: Data from the 2014 to 2021 Korea National Health and Nutrition Examination Survey were analyzed (N = 31,558). MetS was defined according to the criteria by revised NCEP/ATP-III. The domain-specific MVPA was assessed using the K-GPAQ. The LTPA and OPA status were classified into four categories: (1) 0 min/week, (2) 1 to 149 min/week, (3) 150 to 299 min/week, and 4) ≥ 300 min/week. In addition, the present study calculated total MVPA as a sum of OPA and LTPA and further classified it into six groups; (1) 0 min/week, (2) 1 to 149 min/week, (3) 150 to 299 min/week, (4) 300 to 449 min/week, (5) 450 to 599 min/week, 6) ≥ 600 min/week. Results: The ≥ 300 min/week and the 150 to 299 min/week of LTPA showed better outcomes in cardiometabolic disease risk factors and surrogate markers of insulin resistance compared with the 0 min/week of LTPA regardless of adiposity status. Risk of MetS in ≥ 300 min/week of LTPA was lower than in 0 min/week, 1 to 149 min/week, and 150 to 299. In addition, LTPA was significantly associated with a risk of the MetS in a curvilinear dose-response curve, however, no significant effects of a non-linear relationship between OPA and risk of the MetS. Conclusions: Our findings showed that LTPA was associated with a risk of MetS with a dose-response curve, whereas no significant non-linear effects were found between OPA and the risk of MetS. Therefore, the MVPA domain is an independent factor of the risk of MetS.